2013
DOI: 10.12691/aees-1-4-4
|View full text |Cite
|
Sign up to set email alerts
|

Prey Density and Diet of Snow Leopard (Uncia Uncia) In Shey Phoksundo National Park, Nepal

Abstract: The food habit of the snow leopard (Uncia uncia) is not always according to the availability of its prey species. The aim of the study was to estimate wild prey densities in Shey-Phoksundo National Park in relation to diet composition. In addition, the study sought to determine livestock depredation status and its frequency of occurrence in the diet of snow leopards. Population density of blue sheep (Pseudois nayaur) was estimated by vantage point count methods. Densities of other wild prey species were estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
17
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 8 publications
2
17
1
Order By: Relevance
“…A study by Kunwar (2003) in the ACA also recognized the snow leopard as the principal predator where it was responsible for 58% of the total livestock loss. However, he reported seven wild predators in the ACA and Devkota et al (2013) also reported snow leopard as the principal predator where it was responsible for 45.6% of the total livestock depredation in the SPNP, which is quite higher than in our study. The loss to snow leopards in winter is comparable to the results revealed in the ACA by Oli et al (1994), where 39% of the feces of snow leopards collected in winter contained the remains of livestock.…”
Section: Discussioncontrasting
confidence: 74%
See 4 more Smart Citations
“…A study by Kunwar (2003) in the ACA also recognized the snow leopard as the principal predator where it was responsible for 58% of the total livestock loss. However, he reported seven wild predators in the ACA and Devkota et al (2013) also reported snow leopard as the principal predator where it was responsible for 45.6% of the total livestock depredation in the SPNP, which is quite higher than in our study. The loss to snow leopards in winter is comparable to the results revealed in the ACA by Oli et al (1994), where 39% of the feces of snow leopards collected in winter contained the remains of livestock.…”
Section: Discussioncontrasting
confidence: 74%
“…Because of the habitat destruction and other anthropogenic activities, snow leopards are at high risk (Wegge et al, 2012;Devkota et al, 2013), so knowing how these factors influence habitat use is critical to the conservation of snow leopard (Wolf and Ale, 2009). The density of blue sheep (3.8 animals/km 2 ) in the study area as compared to other regions of Nepal, is higher than in the SPNP (2.27 animal/km 2 ; Devkota et al, 2013) and upper region of Mustang district (0.86 animal/km 2 ; Aryal et al, 2014). However, the density of the blue sheep in this study area is quite less than that of 8.4 animals/km 2 in the Phu Valley of Manang district (Wegge et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations